Comparison of Bactericidal Activity of Serum Collected from Typhoid Patients and Normal Human Against Salmonella typhi at Various Incubation Time - Shahriar, Mohammad; Halder, Luke Donald; Nushrat, Nayeema; Hossain, Mahboob; Kabir, ANM Hamidul; Kabir, Shaila (Dhaka University Journal of Pharmaceutical Sciences, 2011)
DOI: 10.3329/dujps.v9i1.7436 Dhaka Univ. J. Pharm. Sci. 9(1): 66-67 2010 (June)